2022
DOI: 10.1002/ajb2.16036
|View full text |Cite
|
Sign up to set email alerts
|

Why honeybees are poor pollinators of a mass‐flowering plant: Experimental support for the low pollen quality hypothesis

Abstract: Premise Honeybees dominate the flower‐visitor assemblages of many plant species, yet their efficiency in terms of the quality of pollen delivered to stigmas is largely unknown. We investigated why honeybees are poor pollinators of Aloe ferox, a self‐incompatible succulent treelet with large numbers of flowers. Honeybees are very frequent visitors to flowers of this species, yet contribute very little to seed production. Methods We assessed pollen loads on honeybees, studied their visitation behavior, selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A comparison between nocturnal hawkmoths and diurnal bees of pollen removal and deposition in L. japonica by single visits showed that pollination effectiveness of hawkmoths was over 10-fold higher than that of bees . Our observations showed that honeybees usually behaved as pollen thieves (see also Diller et al, 2022) given that they were observed trying to collect pollen even from the undehisced anthers. Longitudinally dehiscing anthers in L. japonica with mass pollen presentation (Fig.…”
Section: Floral Scent Rhythmmentioning
confidence: 60%
“…A comparison between nocturnal hawkmoths and diurnal bees of pollen removal and deposition in L. japonica by single visits showed that pollination effectiveness of hawkmoths was over 10-fold higher than that of bees . Our observations showed that honeybees usually behaved as pollen thieves (see also Diller et al, 2022) given that they were observed trying to collect pollen even from the undehisced anthers. Longitudinally dehiscing anthers in L. japonica with mass pollen presentation (Fig.…”
Section: Floral Scent Rhythmmentioning
confidence: 60%
“…An important caveat of transfer efficiency as a measure of pollen economy is that it weights conspecific pollen on stigmas equally, even though pollinators can vary in the quality of pollen that they deposit on stigmas [83]. For the majority of the approximately 37% of angiosperm species that are self-incompatible [84], self-pollination contributes no more to siring success than pollen lost during transport; whereas for species that are self-compatible or have lateacting self-incompatibility, self-pollination can be associated with detrimental effects on ovule fertilization and seed development [85][86][87], reducing both female and male success. Similar qualifications apply to biparental inbreeding.…”
Section: (B) Pollen Transfer Efficiencymentioning
confidence: 99%
“…The final step of the pollination process is fertilization. Vectors may visit flowers of a different plant species or flowers on the same self‐incompatible plant, resulting in pollen transfer without fertilization (Diller et al, 2022). If floral visitors deposit an insufficient number of pollen grains to elicit fertilization, pollination does not occur (Németh and Smith‐Huerta, 2003; Koski et al, 2018).…”
Section: Figurementioning
confidence: 99%